Modelación numérica del desplazamiento generado por del fenómeno bumpy road (2020)
The rotational displacement caused by the 'bumpy phenomenon' in a road is modeled for a system with rotational and linear damping, for the above it is implemented a code in MATLAB. The theoretical model is tested for different situations and it is found that the speed of the vehicle determines the magnitude of the soil reaction while the dimension of the beam affects the behavior of the inclination of angle 0.